Caspase inhibitor z-VAD-FMK increases the survival of hair cells after Actinomycin-D-induced damage in vitro. (27th July 2020) - Chang, Huimin; Sun, Fei; Tian, Keyong; Wang, Weilong; Zhou, Ke; Zha, Dingjun; Qiu, Jianhua
Highlights: Act-D treatment had no obvious damage to SGNs. Act-D treatment induce hair cell loss and apoptosis. z-VAD-FMK against Act-D-induced damage to HCs loss. Abstract: Actinomycin-D (Act-D) is a highly effective chemotherapeutic agent that induces apoptosis in systemic tissues. Act-D combined with other chemotherapeutic agents exhibits ototoxic effects and causes hearing impairment. To investigate the potential toxic effects of Act-D in the inner ear, we treated cochlear organotypic cultures with varying concentrations of Act-D for different durations. For the first time, we found that Act-D specifically induced HC loss and apoptosis in a dose- and time-dependent manner but not neuronal degeneration. Co-treatment with benzyloxycarbonyl-Val-Ala-Asp-fluoromethyl ketone (z-VAD-FMK), a pan cysteine protease inhibitor, significantly reduced HC loss and apoptosis induced by Act-D, indicating increased cell survival. Taken together, Act-D exposure has ototoxic effects on the auditory system, while z-VAD-FMK prevents Act-D-induced hair cell damage.